Insights from Disaggregating the Human Capital Index - World Bank Group (World Bank, Washington, DC, 2020)
The Human Capital Index (HCI is a cross-country metric measuring the human capital that a child born today can expect to attain by her 18th birthday, given the risks of poor health and poor education prevailing in her country. The global HCI is calculated for 157 countries using national averages of the component data. While the cross-country comparison of human capital outcomes is important, national averages mask significant differences along dimensions such as gender, ethnicity, socioeconomic status, and geographic location, which are likely associated with gaps in productivity. This report quantifies some of these human capital inequalities, with a special focus on socioeconomic and subnational spatial differences. The socioeconomic analysis covers 50 low- and middle-income countries where the data permit comparable disaggregation. The spatial analysis covers 11 low- and middle-income countries where the global HCI release sparked demand for analysis at the subnational level. As a result, rather than describing comprehensive trends, this booklet highlights the potential of detailed disaggregation for the design of well-targeted policies.